Simulation of the behavior of different loads in connections of self-supporting flat roof connections with side beams using finite elements (Publicaciones en Ciencias y Tecnología, 2022)
The different alternatives used in the construction industry make that in the structural analysis and design several tools are used to know the correct behavior of the structures under different load states. Therefore, a study of the behavior of self-supporting flat roofs and their connection with lateral beams is presented by applying the finite element method within a linear analysis with the help of ANSYS Workbench software. For this purpose, an IMAP-800 section was used, forming roofs with spans of 10, 20, 30 and 40 m, complementing the analysis with lattice-type beams and columns. For the fastening support, a plate with thicknesses from 4 to 12 mm was used, to compare with national and international design guidelines, such as thickness, slope, maximum span and the geometry of the fastening support. Maximum stresses were observed near the fixing brackets, while maximum deformations took place at the ends of the roof. By setting new parameters to save the corresponding spans, it showed an increase in the roof weight of about 5% in relation to the design guidelines used.
Keywords: simulation software; fixing bracket; flat self-supporting roof; finite elements